COMPARISON OF PROPP’S SPHERES OF ACTIONS IN DOCTOR STRANGE SEQUEL MOVIES - Mevia, Firzasheylla Herita; Budiwaty, Suci (UG Journal, 2025)
This research was conducted to prove that Vladimir Propp's Spheres of Action can be used in modern movies. It provides insight into whether the classical narrative structure identified by Propp is still relevant and applicable in the context of modern superhero movies. This research aimed to find the seven types of spheres of action from Doctor Strange (2016) and Doctor Strange in the Multiverse of Madness movies and compare the data findings based on Vladimir Propp's theory. This research used a qualitative method. The results of the research showed that there were six out of seven types of spheres of action found in Doctor Strange (2016) and Doctor Strange in the Multiverse of Madness. namely, Doctor Strange as a Hero, Kaecillius and Dormammu as Villains, The Ancient One as Dispatcher, Jonathan Pangborn, Wong, The Ancient One, and Christine Palmer as Donors, Wong and Karl Mordo as Helpers, and Kaecillius as a False Hero. Meanwhile in Doctor Strange in the Multiverse of Madness movie, the results of the research are Doctor Strange as a Hero, and a Maximmof as a Villain, America Chavez as a Dispatcher, Wong, Christine Palmer, Charles Xavier, America Chavez and Doctor Strange as Donors, Wong and America Chavez as Helpers, and lastly Karl Mordo as a False Hero. The Villains in both movies are different characters. The Dispatcher also has different characters. 4 Donors in Doctor Strange (2016) movie, and 5 Donors in Doctor Strange in the Multiverse of Madness movie. 3 Helpers in Doctor Strange (2016) and 2 Helpers in Doctor Strange in the Multiverse of Madness movie. The Hero is the same, and the False Heroes in both movies are different characters.